2011
DOI: 10.1177/0273475311420245
|View full text |Cite
|
Sign up to set email alerts
|

Intradepartmental Faculty Mentoring in Teaching Marketing

Abstract: Teaching continues to be less valued than research (e.g., Sharma, Albers-Miller, Pelton, & Straughan, 2006), even though a strong teaching performance also increases research productivity (Baxter Magdola, 1999; Stack, 2003), and despite constant calls to improve the quality of teaching in higher management education (see Schibrowsky, Peltier, & Boyt, 2002; Van Fleet & Peterson, 2005). Van Fleet and Peterson (2005) encourage the use of a peer-review process for teaching by involving peers from other academic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 67 publications
(113 reference statements)
0
7
0
Order By: Relevance
“…Wichita State mentees believed that the program provided a venue to safely discuss concerns that they had. Earlier research showed similar benefits for mentees in university settings (Benson et al, 2002;Tähtinen, Mainela, Nätti, & Saraniemi 2012;Wake Forest School of Medicine, 2015).…”
Section: Benefitsmentioning
confidence: 83%
“…Wichita State mentees believed that the program provided a venue to safely discuss concerns that they had. Earlier research showed similar benefits for mentees in university settings (Benson et al, 2002;Tähtinen, Mainela, Nätti, & Saraniemi 2012;Wake Forest School of Medicine, 2015).…”
Section: Benefitsmentioning
confidence: 83%
“…Intradepartmental mentoring can improve faculty retention, increase all types of performance, and lower the detrimental effects of rejection sensitivity (Day & Porter, 2017). A supportive mentoring environment requires organizational support (e.g., rewarding faculty who participate), a knowledge sharing environment (e.g., brown bag lunches or colloquiums), and an honest feedback process (e.g., periodic assessments by administrators and faculty mentors; Tähtinen, Mainela, Nätti, & Saraniemi, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This research followed the principles of self-ethnography, which has been utilized previously in marketing education and in a business school setting (Tähtinen et al, 2012). Self-ethnography is a method defined as “a study and a text in which the researcher-author describes a cultural setting to which s/he has a ‘natural access’, [and] is an active participant” (Alvesson, 2003, p. 174).…”
Section: Methodsmentioning
confidence: 99%